The Prognostic Value of Troponin in Pediatric Polytrauma - Braun, Christian Karl; Schaffer, Annika; Weber, Birte; Huber-Lang, Markus; Kalbitz, Miriam; Preßmar, Jochen (Frontiers in Pediatrics, 2019)
Introduction Severe trauma accounts for a great number of deaths among children and adolescents. The diagnostic value of troponin serum levels of severely injured patients has been reported for adults, but data on pediatric polytrauma is scarce. Therefore, we conducted a retrospective monocentered study analysing the prognostic value of troponin T in pediatric trauma patients at the time point of hospital admission. Methods Data of 88 polytraumatized pediatric patients admitted to the emergency room of the University Hospital of Ulm, Germany between 2007 and 2016 were analyzed retrospectively. The data source was the written and digital patient records. Interleukin 6 (IL-6), creatine-kinase activity (CK-activity), lactate and troponin T (TnT) levels were measured by a certified clinical diagnostic laboratory and patients were stratified for the Injury Severity Score (ISS). The prognostic value for lung contusion, organ dysfunction and fatal outcome was statistically explored. The study was approved by the independent ethical committee of the University of Ulm (#44/18). Results TnT levels were significantly increased in patients after severe polytrauma (PT) compared to mild or moderate trauma severity as assessed by ISS values. Patients with TnT levels above the cut-off showed significantly increased levels of IL-6 and CK-activity and a significantly prolonged stay on the intensive care unit. However, TnT levels did not correlate with absolute ISS values. TnT levels were significantly increased in patients with chest trauma and lung contusion. The incidence of lung contusion was associated with elevation of TnT. So was the onset of organ dysfunction as defined as a SOFA score ≥2 and fatal outcome, with a significant enhancement of plasma levels in children with organ dysfunction and in non-survivors. Conclusion Evaluation of troponin T on admission of multiply injured children may help predicting severity of injury and mortality in the clinical course after trauma.